The Effect of Health Literacy on Cardiovascular Health Behaviors Among Adolescents - İsa Çelik; Fatma Dinç; Zennure Arga; Murat Bektaş; Arzu Sarıalioğlu (Genel Tıp Dergisi, 2026)
Aim: This study aimed to evaluate how the level of health literacy influences the cardiovascular health behaviors of adolescents.Materials and Methods: This cross-sectional study was carried out face-to-face with 487 middle school students in a province in eastern Turkey between April and June 2023. Study data were gathered from adolescents through a descriptive information form and the Health Literacy for School-Aged Children Scale (HLSAC), and the Cardiovascular Health Behavior Scale for Children (CHBSC) after obtaining written informed consent from the participants’ parents. To assess the impact of adolescents’ health literacy levels on their cardiovascular health behaviors, a simple linear regression analysis was performed.Results: The mean CHBSC, and HLSAC, scores of adolescents were 62.39 ± 11.12, and 30.14 ± 5.02respectively. The health literacy levels of adolescents explained 4.6% of the change in their cardiovascular health behaviors.Conclusions: This study revealed that adolescents’ health literacy levels have a statistically significant impact on their cardiovascular health behaviors. Interventions designed to enhance health literacy may support the adoption of healthier lifestyle habits for cardiovascular well-being and help lower the risk of cardiovascular diseases in the future.